Differential DNA methylation profiles of coding and non-coding genes define hippocampal sclerosis in human temporal lobe epilepsy. (30th December 2014) - Miller-Delaney, Suzanne F.C.; Bryan, Kenneth; Das, Sudipto; McKiernan, Ross C.; Bray, Isabella M.; Reynolds, James P.; Gwinn, Ryder; Stallings, Raymond L.; Henshall, David C.
Abstract : See Grote et al. (doi:10.1093/awu386 ) for a scientific commentary on this article. Miller-Delaney et al. report the first genome-wide analysis of DNA methylation in the hippocampus of patients with temporal lobe epilepsy. They identify altered methylation profiles in protein-coding genes, reveal pathology grade-specific differences and identify methylation-sensitive non-coding RNAs. The findings increase understanding of mechanisms regulating coding/non-coding gene expression in epilepsy. Abstract : Temporal lobe epilepsy is associated with large-scale, wide-ranging changes in gene expression in the hippocampus. Epigenetic changes to DNA are attractive mechanisms to explain the sustained hyperexcitability of chronic epilepsy. Here, through methylation analysis of all annotated C-phosphate-G islands and promoter regions in the human genome, we report a pilot study of the methylation profiles of temporal lobe epilepsy with or without hippocampal sclerosis. Furthermore, by comparative analysis of expression and promoter methylation, we identify methylation sensitive non-coding RNA in human temporal lobe epilepsy. A total of 146 protein-coding genes exhibited altered DNA methylation in temporal lobe epilepsy hippocampus ( n = 9) when compared to control ( n = 5), with 81.5% of the promoters of these genes displaying hypermethylation. Unique methylation profiles were evident in temporal lobe epilepsy with or without hippocampal sclerosis, in addition to a common methylation profile regardless of pathology grade. Gene ontology terms associated with development, neuron remodelling and neuron maturation were over-represented in the methylation profile of Watson Grade 1 samples (mild hippocampal sclerosis). In addition to genes associated with neuronal, neurotransmitter/synaptic transmission and cell death functions, differential hypermethylation of genes associated with transcriptional regulation was evident in temporal lobe epilepsy, but overall few genes previously associated with epilepsy were among the differentially methylated. Finally, a panel of 13, methylation-sensitive microRNA were identified in temporal lobe epilepsy including MIR27A, miR-193a-5p ( MIR193A ) and miR-876-3p ( MIR876 ), and the differential methylation of long non-coding RNA documented for the first time. The present study therefore reports select, genome-wide DNA methylation changes in human temporal lobe epilepsy that may contribute to the molecular architecture of the epileptic brain.